PENGARUH BAURAN PEMASARAN TERHADAP KEPUTUSAN PEMBELIAN MINYAK GORENG SARI MURNI (JURNAL ECONOMICA : Research of Economic And Economic Education, 2012)
Besides the issue of product, pricing and distribution of cooking oil Sari Murni, the promotion is also an important issue that should also be considered to introduce Sari Murni cooking oil to the public. Since the promotion is an activity to introduce a product to consumers, such as through advertising, direct sales, sales promotion or through this publicity, this research using causal design research. According to Umar (2009:139) that a causal research design is a useful research to analyze the relationships between one variable with another variable. The research shows, that are significant influences between products, price, promotion, and distribution to consumer decision to buy Sari murni